The Influence of Knowledge, Motivation, and Attitude Toward The Behavior of Housewife to Eradicate of Aedes Aegepty Mosquito Nest (PSN) (Public Health Perspective Journal, 2018)
Semarang city is the region with the highest dengue hemorrhagic fever cases in central java province. Eradication of aedes aegepty mosquito nest is one of the efforts considered appropriate in the prevention and eradication of dengue hemorrhagic fever. The active participation of housewives is necessary, the participation of housewives depends on the knowledge, motivation, and attitudes of the community towards the disease and its prevention. The purpose of this research is to analyze the influence of knowledge, motivation, and attitude toward the behavior of housewife to eradicate aedes aegepty mosquito nest (PSN). This research methos is quantitative with cross sectional design.Population of all housewives in Bulustalan Village Semarang, the sample amounted to 90 samples using purposive sampling technique. The results showed that there was an influence between knowledge on the behavior of mosquito nest eradication (p = 0,000). There is an influence between motivation to the behavior of mosquito nest eradication value (p = 0.012). There is an influence between attitudes toward the behavior of mosquito nest eradication value (p = 0.000). Logistic regression results showed that the more dominant knowledge influenced the behavior of mosquito nest eradication (p = 0,008) and Exp (B) value 4,365. The conclusion of housewife who has knowledge, motivation, and good attitude affect the behavior of housewife to eradicate aedes aegepty mosquito nest (PSN)Â